Effectiveness of sensory integration program in motor skills in children with autism - Amel E. Abdel Karim; Amira H. Mohammed (Egyptian Journal of Medical Human Genetics, 2015)
Background: Autism spectrum disorders (ASDs) represent an extensive category of conditions that had a variety of deficits. Dysfunctions of perceptual and sensory processing as well as interaction and neurological functioning result in various functional behavior limitations. Aim: The present study aimed to determine the effectiveness of sensory integration program in children with autism. Methods: Thirty-four children from both sexes suffering from autism spectrum disorders (ASDs) participated in this study. Their age ranged from 40 to 65 months with mean age 53.21 ± 6.87 months. The children were tested pre and post treatment using the Peabody Developmental Motor Scale (PDMS-2) to assess gross and fine motor skills and to identify the effectiveness of sensory integration on the developmental skill levels. Each child received sensory integration program. The sensory integration program was conducted three sessions per week for 6 months. Results: Comparing the pre and post treatment mean values of the variables measured using PDMS-2, revealed significant improvement in gross and fine motor skills. Conclusion: The sensory integration therapy was effective in the treatment of autistic children as it helps those children to become more independent and participate in everyday activities.